Why do greater forest tenure rights not enthuse local communities? An early observation on the new community forestry scheme in state forests in Indonesia - Ragandhi, Arsad; Hadna, Agus Heruanto; Setiadi, Setiadi; Maryudi, Ahmad (Forestry Faculty, Universitas Hasanuddin, 2021)
The Indonesian Ministry of Environment and Forestry recently issued a 35-year permit-based social forestry, called Izin Pemanfaatan Hutan Perhutanan Sosial (IPHPS), which was implemented in forestlands managed by the State Forest Corporation (SFC). IPHPS is a unique scheme because social forestry permits were previously granted on forestland unencumbered with rights. It provides more secure tenure rights (long-term permits), greater decision-making authority, and improved profit-sharing arrangements compared with the SFC’s co-management model. However, IPHPS has not attracted widespread interest from local communities. This paper aims to identify and to analyse factors that explain local communities’ low interest in the policy. Results show that local communities have not been attracted by the scheme because it requires them to undertake substantial investments in reforestation and make several payments to the government beyond their means. This paper highlights the specific challenges related to access mechanisms and benefits to local communities from the granted rights. Lastly, local communities were prone to manipulative persuasion by the SFC to continue the co-management model.